"Salted Silica": Sol‐Gel Chemistry of Silica under Hypersaline Conditions1. Issue 3 (29th January 2014) - Nisticò, Roberto; Magnacca, Giuliana; Antonietti, Markus; Fechler, Nina
Abstract In a facile one‐step approach, high surface area mesoporous silica powders are synthesized using ordinary salts for pore and morphology control during the sol‐gel process. Applying tetraethyl orthosilicate (TEOS) as a reference system, the addition of high salt loads such as NaCl and ZnCl2 results in highly increased surface areas of up to 750 m2 g–1, predominantly in the mesopore range Besides the surface area, the pore volume and the pore size can be controlled by the salt amount as well as the salt nature, reaching values of 1.1 cm3 g–1 and 14 nm, respectively. Compared to standard processes, the herein presented synthesis is extremely simple: it only comprises the dissolution of TEOS and the respective salt in 1 M HCl, followed by solvent evaporation, salt removal through simple washing with water and drying. This way, no special equipment is required, no organic templates are to be employed, and the overall approach is highly efficient and sustainable.